Upside down : a novel - Steel, Danielle (Delacorte Press, 2024)
"Oscar-winning actress Ardith Law is a Hollywood icon. Radiant at sixty-two, she is the epitome of glamour and a highly respected artist. But her success has come at a price: She has a strained relationship with her daughter, Morgan, who at thirty-eight still blames Ardith for putting her career before being a mother. Morgan is a successful plastic surgeon in New York City--and the distance from Ardith's Bel Air mansion is not lost on either of them. Ardith became a single mother when Morgan was seven, after her unfaithful husband died in a helicopter accident. In recent years, she has found amiable companionship with fellow actor Bill West. But Ardith's comfortable world is turned upside down when she hires a temporary personal assistant, Josh Gray, while Bill is away filming in London. Josh's rough-around-the-edges persona is the opposite of what Ardith is used to, but an unexpected tragedy brings them closer, stirring up conflicting feelings in her for this younger man. In New York, Morgan is swept off her feet by world-renowned TV anchorman Ben Ryan. Though more than two decades her senior, Ben is handsome, charismatic, and just as smitten as Morgan. But when a blackmail scheme puts his career--and their relationship--on the line, Morgan doesn't know where to turn. Perhaps . . . to her mother? As each woman navigates an unconventional romance, they cautiously approach each other on new terms and attempt to put aside their past for a new future. In Upside Down, Danielle Steel tells an unforgettable story of bold choices, second chances, and the hope of reconciliation" --